2005
DOI: 10.1292/jvms.67.275
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Treatment at CIDR Insertion Influences Ovarian Follicular Dynamics in Japanese Black Cows

Abstract: ABSTRACT. Ovarian follicular dynamics and estrous synchronization after Gonadotropin-releasing hormone (GnRH) treatment at Controlled Internal Drug Releasing device (CIDR) insertion were investigated in Japanese Black cows. CIDR was inserted for eight cows at 7 days after estrus. Cows were allocated to either Group A: 8-day CIDR insertion with GnRH treatment on d 0 (n=4, d 0=CIDR insertion) or Group B: 8-day CIDR insertion (n=4). Both groups were injected with prostaglandin F 2α (PGF 2α ) on d 7. Ultrasonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…By contrast, in heifers with CL on day 0, intermediate ovulation was limited (CIDR-treated group: 21.4%, No-CIDR-treated group: 39.1%). This result may due to that CIDR insertion with GnRH treatment induces intermediate ovulation of the existing dominant follicle [1] and forms new CL [2]. However, on the whole, CIDR insertion suppressed the intermediate ovulation during initial 7 days induced by GnRH treatment as compared to No-CIDR-treated group in the present study (CIDR-treated group: 33.3%, No-CIDRtreated group: 52.6%, P<0.05).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…By contrast, in heifers with CL on day 0, intermediate ovulation was limited (CIDR-treated group: 21.4%, No-CIDR-treated group: 39.1%). This result may due to that CIDR insertion with GnRH treatment induces intermediate ovulation of the existing dominant follicle [1] and forms new CL [2]. However, on the whole, CIDR insertion suppressed the intermediate ovulation during initial 7 days induced by GnRH treatment as compared to No-CIDR-treated group in the present study (CIDR-treated group: 33.3%, No-CIDRtreated group: 52.6%, P<0.05).…”
Section: Discussioncontrasting
confidence: 61%
“…GnRH induced the intermediate ovulation even during the period of CIDR insertion. Ando, et al reported that the ovulation was not induced during CIDR insertion without GnRH treatment at CIDR in [2]. These results indicated that CIDR insertion with GnRH treatment on day 0 probably does not affect intermediate ovulation induced by GnRH in heifers without functional CL on day 0, however CIDR tends to suppress intermediate ovulation in heifers with functional CL on day 0 together with existent CL.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the time interval to ovulation confirmation after PRID removal was 72.0-72.1 h in 4/5 cows in the synchronized AI group (73.2 Ϯ 2.7 h). Ando et al (2005) reported that ovarian follicular dynamics and estrus synchronization occurred after GnRH treatment at CIDR insertion in Japanese Black cows. The time interval to ovulation after CIDR removal was 72 h in the group that showed ovulations both intermediately during CIDR insertion and after CIDR removal.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the time interval to ovulation confirmation after PRID removal was 72.0–72.1 h in 4/5 cows in the synchronized AI group (73.2 ± 2.7 h). Ando et al . (2005) reported that ovarian follicular dynamics and estrus synchronization occurred after GnRH treatment at CIDR insertion in Japanese Black cows.…”
Section: Resultsmentioning
confidence: 99%